2018
DOI: 10.3892/or.2018.6770
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase SIRT6 regulates chemosensitivity in liver cancer cells via modulation of FOXO3 activity

Abstract: Liver cancer is the leading cause of cancer-related mortality worldwide and its incidence is increasing. Considerable effort has been made in recent decades to improve the diagnosis and treatment of liver cancer. Advanced liver cancer often exhibits a poor response to chemotherapy and poor prognosis due to acquired chemoresistance and tumor recurrence. Understanding the precise molecular mechanisms that are responsible for chemotherapeutic drug-induced cell death could potentially identify novel therapeutic ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…For example, SIRT6 is downregulated in DOX-treated liver cancer cells, contributing to DOX-induced cell death. The pro-survival role of SIRT6 in this model, as demonstrated by the overexpression of the enzyme, is mediated by Foxo3 degradation [59]. Inhibition of SIRT6 also sensitizes cancer cells to chemotherapy [60].…”
Section: Discussionmentioning
confidence: 85%
“…For example, SIRT6 is downregulated in DOX-treated liver cancer cells, contributing to DOX-induced cell death. The pro-survival role of SIRT6 in this model, as demonstrated by the overexpression of the enzyme, is mediated by Foxo3 degradation [59]. Inhibition of SIRT6 also sensitizes cancer cells to chemotherapy [60].…”
Section: Discussionmentioning
confidence: 85%
“…In addition, SIRT6 downregulation is required for the chemosensitivity of HCC cells to doxorubicin treatment, which works through increasing the nuclear localization and activation of forkhead box O3 (FoxO3) to trigger proapoptotic target gene expression. When FoxO3 is absent, SIRT6 overexpression was found not able to prevent HCC cell death 77,127 . Independently, SIRT6 was demonstrated to potentiate the EMT, which is considered as the leading cause of poor prognosis for HCC, by deacetylating Beclin‐1 to promote of the autophagic degradation of E‐cadherin 76 .…”
Section: Human Diseasesmentioning
confidence: 99%
“…Sirtuin 6 (SIRT6) combines and interacts with FOXO3 to regulate FOXO3 deacetylation, and it increases FOXO3 ubiquitination and phosphorylation at site S253, which is critical for FOXO3 degradation. Acetylation affects kinase binding to FOXO3 and leads to the apoptotic effects of FOXO3 that are independent of SIRT6 downregulation (94). TGF-b induces FOXO3 activation through specific dephosphorylation at Thr32, which is regulated by casein kinase I-ϵ (CKI-ϵ) (93).…”
Section: Foxo Proteins In Hccmentioning
confidence: 99%
“…Notas et al (116) observed that the binding of a proliferation-inducing ligand to B-cell maturation antigen activated the JNK2/FOXO3/GADD45 signaling pathway and induced G 2 /M arrest. Furthermore, Hu et al (94) reported that high SIRT6 expression and low FOXO3 expression after DOX treatment led to TACE resistance. In subsequent experiments, overexpression of SIRT6 did not prevent DOX-induced death in the context of FOXO3-knockdown (94).…”
Section: Foxo3 In Hccmentioning
confidence: 99%